Correction: Identification of potential serum biomarkers of acute paraquat poisoning in humans using an iTRAQ quantitative proteomic. Issue 7 (28th January 2019) - Wei, Liming; Wang, Yi; Lin, Ling; Zhang, Lei; Shi, Yan; Xiang, Ping; Cao, Shujun; Shen, Min; Yang, Pengyuan
Abstract : Correction for 'Identification of potential serum biomarkers of acute paraquat poisoning in humans using an iTRAQ quantitative proteomic' by Liming Wei et al., RSC Adv., 2018, 8, 10598–10609.